Utilization of 1H-Indole-3-carboxaldehyde as a Precursor for the Synthesis of Bioactive Indole Alkaloids - El-Sawy, Eslam R.; Abdelwahab, Ahmed B.; Kirsch, Gilbert (Synthesis, 2018)
Indole alkaloids constitute a large class of natural products and their diverse and complex structures have been attributed to potent biological activities such as anticancer, anti-inflammatory, antimicrobial, antimalarial, antiplasmodial and protein kinase inhibition. The isolation of bioactive compounds from natural sources is difficult, costly and an extremely time-consuming process, therefore synthetic pathways are more convenient than natural separation to deliver such compounds in considerable amounts. In this respect, this review provides comprehensive information on the structures and the synthesis of bioactive indole alkaloids utilizing 1H-indole-3-carboxaldehyde and its derivatives as starting compounds. 1 Overview2 Phytoalexins2.1 Brassinin, Cyclobrassinin and Brassitin2.2 1-Methoxybrassinin, 1-Methoxyspirobrassinol and 1-Methoxyspirobrassinin2.3 4-Methoxybrassinin and 4-Methoxycyclobrassinin2.4 Cyclobrassinone2.5 Brassilexin2.6 (S)-(–)-Spirobrassinin2.7 Camalexin3 Bis(indole) Alkaloids: Rhopaladines A–D4 Coscinamides A and B5 α-Cyclopiazonic Acid6 Dipodazine7 Isocryptolepine8 Apparicine9 Carbazole Alkaloids: Mukonine and Clausine E10 Indolmycin11 Conclusion
Keywords: indoles; 1H-indole-3-carboxaldehyde; synthesis; alkaloids; bioactivity